Obesity – a great public health problem - Nowicka, Grażyna (Studia Ecologiae et Bioethicae, 2005)
Obesity affecting more than 30% of adult population has been recognized as a major public health problem. Overweight and obesity generally are caused by unhealthy eating patterns and a lack of physical activity. Managing of obesity and overweight is of paramount importance because of well established relations between excess body mass and different diseases such as coronary heart disease, type 2 diabetes, hypertension, and some types of cancer. Guidelines for reducing the risk of obesity and obesity-related disorders by dietary changes, increased physical activity and other lifestyle practices have been prepared by healthcare professionalists. WHO prepared the draft of global strategy on diet, physical activity and health, which should be adopted and developed at regional and national levels. Appropriate public knowledge on relationship between diet, physical activity, obesity and health provides a base for prevention of obesity and obesity related disorders.